Diverging Mitigation Strategies of Indonesia's Ulama Council in Majority and Minority Muslim Regions - Nasruddin Yusuf; Ridwan Jamal; Faradila Hasan; Naskur Bilalu (Pascasarjana UIN ANTASARI Banjarmasin, 2026)
Local deviant sects persist across Indonesia's religiously plural regions despite repeated fatwa declarations and enforcement efforts. Prior scholarship has examined MUI's authority and fatwa compliance mainly from a national vantage point, leaving the question of how demographic context shapes mitigation strategy underexplored. This study compares how MUI in Muslim-majority North Sumatra and Muslim-minority North Sulawesi each designs its response to local deviant sects, and asks which approach works under what conditions. Data were gathered through in-depth interviews with MUI officials at the provincial, district, and city levels in both regions, combined with fatwa document analysis and institutional reports. Informants were selected purposively. Source and time triangulation ensured data validity; analysis followed the Miles and Huberman model. North Sumatra MUI relies on a structural-corrective approach backed by formal fatwa decisions and close supervision. This proves effective at enforcing doctrinal boundaries but tends to harden resistance and strengthen internal solidarity among targeted groups. North Sulawesi MUI takes a dialogical-educational route, preserving plural harmony at the cost of slower doctrinal change. In both regions, MUI effectiveness hits the same ceiling: government intervention arrives only after formal legal violations occur, stretching the mitigation timeline and diluting preventive effectiveness. The demographic position of Muslims in a region determines which tools are available, which risks are tolerable, and what counts as success. Mitigation strategy cannot be standardized. The study contributes an adaptive, context-sensitive model of religious governance to the comparative study of Islamic institutions in Southeast Asia